Decoding Food Labels: Handouts for People with Food Allergies - Amy H. Simonne; Elizabeth Gollub (EDIS)
Revised! FCS-8786, a 14-page document by Amy Simonne and Elizabeth Gollub, presents visually appealing handouts that can help people with food allergies quickly scan food labels for the foods they are allergic to. Revised to include information on fish and shellfish allergies. Published by the UF Department of Family, Youth and Community Sciences, December 2007.